Clinical application of voriconazole in pediatric patients: a systematic review - Lin Hu; Juanjuan Huang; Yanfei Li; Gefei He (BMC, 2024)
Abstract The purpose of this study was to review the literature on the clinical use of voriconazole (VRC) in pediatric patients. MEDLINE, Embase, PubMed, Web of Science, and Cochrane Library were searched from January 1, 2000, to August 15, 2023 for relevant clinical studies on VRC use in pediatric patients. Data were collected based on inclusion and exclusion criteria, and a systematic review was performed on recent research related to the use of VRC in pediatric patients. This systematic review included a total of 35 observational studies among which there were 16 studies investigating factors influencing VRC plasma trough concentrations (Ctrough) in pediatric patients, 14 studies exploring VRC maintenance doses required to achieve target range of Ctrough, and 11 studies focusing on population pharmacokinetic (PPK) research of VRC in pediatric patients. Our study found that the Ctrough of VRC were influenced by both genetic and non-genetic factors. The optimal dosing of VRC was correlated with age in pediatric patients, and younger children usually required higher VRC doses to achieve target Ctrough compared to older children. Establishing a PPK model for VRC can assist in achieving more precise individualized dosing in children.